2004
DOI: 10.1023/b:jmsm.0000046387.70323.41
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterisation of a bone defect model filled with ceramic cements

Abstract: Ceramic bone substitute materials are often used to fill defects in comminuted articular fractures. In an in vivo study [1], calcium phosphate cements have been injected into highly loaded slot defects in the proximal tibial metaphysis. During healing, cracks were formed mostly in the proximal anterior aspect of the implanted cement and wedge-like gaps formed between the tibial plateau and the cement. Mechanical ex vivo tests were done to investigate the mechanical competence of the bone cement in such a defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…Further details on the major properties of Norian SRS ® are available elsewhere [203,402]. Besides, the interested readers are suggested to get through the mechanical characterization of a bone defect model filled with ceramic cements [200].…”
Section: The Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further details on the major properties of Norian SRS ® are available elsewhere [203,402]. Besides, the interested readers are suggested to get through the mechanical characterization of a bone defect model filled with ceramic cements [200].…”
Section: The Mechanical Propertiesmentioning
confidence: 99%
“…Since this material is weak under tensile forces, these cements can only be used either in combination with metal implants or in non-load bearing (e.g., craniofacial) applications [137,[197][198][199]. This is confirmed by the mechanical characterization of a bone defect model filled with ceramic cements [200].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that the poor mechanical properties of CPCs under the physiologically relevant conditions of cyclic loading with a significant shear component 52 limit their use to nonload-bearing applications. 6,19 The weak shear and torsional properties of these materials have been attributed to their inherent brittleness; however, there are limited toughness and fatigue data.…”
mentioning
confidence: 99%
“…Since this biomaterial is weak under tensile forces, such formulations can only be used either in combination with metal implants or in non-load bearing (e.g., craniofacial) applications [4,5,160,225]. This is confirmed by the mechanical characterization of a bone defect model filled with bioceramic cements [226]. To conclude this part, one must stress, that chemical Equations (1)-(6) for setting processes are valid for the in vitro conditions only.…”
Section: General Information and Knowledgementioning
confidence: 99%
“…Additional details on the major properties of Norian SRS ® are available elsewhere [231,452]. Besides, the interested readers are suggested to get through the mechanical characterization of a bone defect model filled with ceramic cements [226].…”
Section: Nonporous Formulationsmentioning
confidence: 99%